A high thermal conductivity graphene thermal control film with a weldable layer and a preparation method thereof

By introducing nanodiamond and nanoSiC particles into graphene thermal control film and adding modified metal nanomaterials to the upper and lower layers, the problems of low thermal conductivity and difficulty in welding in composite materials are solved, and high thermal conductivity is achieved Improved performance and welding capabilities, suitable for electronic devices and thermal control technology.

CN116001377BActive Publication Date: 2024-12-13XIJING UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202310065060.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-01-15
Publication Date
2024-12-13
Estimated Expiration
2043-01-15

AI Technical Summary

Technical Problem

The random dispersion of existing graphene sheets in composite materials leads to low thermal conductivity and cannot be directly soldered with solder, which affects its application in electronic devices and thermal control technology fields.

Method used

The high thermal conductive graphene thermal control film adopts a three-layer structure. The intermediate layer is a graphene layer with modified graphene, nanodiamond and nanoSiC particles. The upper and lower layers are graphene modified nanotitanium, graphene modified nanonier and The weldable layer of graphene modified nanocadmium is formed by electrostatic spraying and high-temperature and high-pressure sintering to achieve improved thermal conductivity and welding capabilities.

Benefits of technology

The thermal conduction efficiency and welding performance of graphene thermal control film are significantly improved, allowing it to be soldered directly with solder, and are suitable for thermal management materials with high thermal conductivity.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116001377B_ABST
    Figure CN116001377B_ABST
Patent Text Reader

Abstract

The present invention relates to the technical field of thermal management materials, and specifically discloses a high thermal conductivity graphene thermal control film with a weldable layer and a preparation method thereof, wherein the graphene thermal control film comprises a three-layer structure arranged in sequence, wherein the middle layer structure is a graphene layer, and both the upper and lower layers are weldable layers; the graphene layer is prepared from modified graphene, nano-diamond particles and nano-SiC particles, wherein the modified graphene is obtained by modifying graphene oxide with nematic liquid crystal and reducing it at high temperature, and the graphene oxide comprises graphene powder A with a particle size of 0.01 to 1 μm and graphene powder B with a particle size of 0.5 to 3 μm; the raw material of the weldable layer comprises graphene-modified nano-titanium, graphene-modified nano-nickel and graphene-modified nano-cadmium. In the present invention, a high thermal conductivity graphene thermal control film with a weldable layer has high thermal conductivity and can be directly welded with solder.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of thermal management materials, and in particular to a high thermal conductivity graphene thermal control film with a weldable layer and a preparation method thereof. Background Art

[0002] With the rapid development of science and technology, thermal management systems are increasingly used in modern industry, electronic equipment and other fields, playing an important role in the dispersion, conversion and storage of thermal energy. Among them, thermal management materials are the core of thermal management systems. Therefore, the design and preparation of new thermal management materials with high thermal conductivity has become one of the key issues in promoting the development of science and technology. Among many thermal conductive materials, graphene has a high thermal conductivity of 5300W m -1 K -1 Graphene film materials have attracted widespread attention due to their intrinsic thermal conductivity and excellent mechanical properties, and graphene film materials are considered to be an ideal choice for new thermal management materials due to their high electrical conductivity, high thermal conductivity and high mechanical properties.

[0003] However, existing graphene sheets are often randomly dispersed in composite materials, resulting in large thermal resistance in the system, which leads to low thermal conductivity of composite materials and needs to be improved. In addition, existing graphene films cannot be directly welded with solder, which inevitably leads to connection problems, thus affecting the application and promotion of graphene films in the fields of electronic devices and thermal control technology.

[0004] Therefore, there is an urgent need for a graphene film with high thermal conductivity and capable of being directly soldered with solder. Summary of the invention

[0005] In view of the shortcomings of the prior art, the object of the present invention is to provide a high thermal conductivity graphene thermal control film with a weldable layer which has high thermal conductivity and can be directly welded with solder, and a preparation method thereof.

[0006] In order to achieve the above object, the present invention specifically adopts the following technical solutions:

[0007] A high thermal conductivity graphene thermal control film with a weldable layer, comprising a three-layer structure arranged in sequence, wherein the middle layer structure is a graphene layer, and the upper and lower layers are both weldable layers;

[0008] The graphene layer is prepared from modified graphene, nano-diamond particles and nano-SiC particles, wherein the modified graphene is obtained by modifying mixed graphene oxide with nematic liquid crystal and reducing it at high temperature, and the mixed graphene oxide includes graphene powder A with a particle size of 0.01 to 1 μm and graphene powder B with a particle size of 0.5 to 3 μm;

[0009] The raw materials of the weldable layer include graphene-modified nano-titanium, graphene-modified nano-nickel and graphene-modified nano-cadmium.

[0010] Furthermore, the graphene layer is prepared by the following method: 70 to 99 parts by weight of modified graphene is placed in anhydrous ethanol, and after shaking, a modified graphene suspension is prepared; 0.5 to 1 parts of nano-diamond particles and 0.1 to 1 parts of nano-SiC particles are placed in the suspension in sequence; after shaking, the suspension is electrostatically sprayed on a metal substrate; the suspension is peeled off in water; and finally, the graphene layer is formed by high temperature and high pressure reduction at 1800 to 2500°C.

[0011] Furthermore, the modified graphene is prepared by the following method: mixing graphene powder A and graphene powder B in a weight ratio of 1:1 to obtain mixed graphene oxide, adding the mixed graphene oxide to anhydrous ethanol to prepare a suspension, adding nematic liquid crystal to the suspension, stirring at 40-50° C. for 1-2 hours, and drying at 65-75° C. to obtain the modified graphene; and the weight ratio of the mixed graphene oxide to the nematic liquid crystal is 1:(1.5-2);

[0012] The nematic liquid crystal is one of nematic liquid crystal A, nematic liquid crystal B, and nematic liquid crystal C; the molecular formula of nematic liquid crystal A is as follows:

[0013]

[0014] The molecular formula of nematic liquid crystal B is as follows:

[0015]

[0016] The molecular formula of nematic liquid crystal C is as follows:

[0017]

[0018] Furthermore, the graphene layer has a thickness of 10 μm to 5 cm and a density of 1.1 to 2.5 g / cm 3 , thermal conductivity is between 800 and 2500 W / (m·K).

[0019] Furthermore, the nano-diamond particles have a particle size of 40-100 nm, a thermal conductivity of 2000-2500 W / (m·K), and an expansion coefficient of 1.3-2.3×10 -6 K -1 ;

[0020] The particle size of the nano-SiC particles is 40-100 nm, the thermal conductivity is 200-400 W / (m·K), and the expansion rate is 1×10 -6 K -1 ~5×10 -6 K-1 .

[0021] Furthermore, the weight ratio of graphene-modified nano-titanium, graphene-modified nano-nickel and graphene-modified nano-cadmium in the weldable layer is 1:1:1.

[0022] Furthermore, the graphene-modified nano-titanium is prepared by the following method: firstly, 10-15% by mass of graphene oxide is put into an ethanol solution, ultrasonically vibrated to form a suspension, then 85-90% by mass of nano-titanium oxide is put into the suspension and ultrasonically vibrated, and then the graphene-modified nano-titanium is obtained after drying.

[0023] Furthermore, the graphene-modified nano-nickel is prepared by the following method: firstly, 10-15% of graphene oxide by mass is put into an ethanol solution, ultrasonically vibrated to form a suspension, then 85-90% of nano-nickel by mass is put into the suspension and ultrasonically vibrated, and the graphene-modified nano-nickel is obtained after drying.

[0024] Furthermore, the graphene-modified nano-cadmium is prepared by the following method: firstly, 10-15% of graphene oxide by mass is put into an ethanol solution, ultrasonically vibrated to form a suspension, then 85-90% of nano-cadmium by mass is put into the suspension and ultrasonically vibrated, and the graphene-modified nano-cadmium is obtained after drying.

[0025] A method for preparing a high thermal conductivity graphene thermal control film with a weldable layer comprises the following steps: mechanically pressing the weldable layer into a target material for magnetron sputtering, and then magnetron sputtering the target material onto the upper surface and the lower surface of the graphene layer respectively, so as to obtain the graphene thermal control film.

[0026] Compared with the prior art, the present invention has the following technical effects:

[0027] The graphene layer used in the present invention is prepared by uniformly mixing graphene powder, nano-diamond and nano-SiC particles in anhydrous ethanol by ultrasonic mixing, so that the nano-diamond can be embedded between the graphene sheets during the sintering process, thereby enhancing the heat conduction efficiency between the sheets, thereby effectively improving the heat conduction efficiency of the graphene thermal control film.

[0028] The modified graphene used in the graphene layer of the present invention has a high degree of orientation during the high-temperature sintering process due to the use of nematic liquid crystal modification, thereby enhancing the thermal conductivity in the orientation direction, so that the small-particle powder can enhance the thermal conductivity perpendicular to the orientation direction on the plane, thereby greatly improving the thermal conduction efficiency of the graphene thermal control film.

[0029] In the present invention, both upper and lower surfaces of the graphene layer are provided with weldable layers, and the system used for the weldable layer can be combined with the graphene layer, thereby realizing direct welding of high thermal conductivity graphene and solder. In this way, a high thermal conductivity graphene thermal control film with a weldable layer in the present invention has high thermal conductivity and can be directly welded with solder. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] Figure 1 This is a schematic structural diagram of a high thermal conductivity graphene thermal control film with a weldable layer according to Example 1 of the present invention;

[0031] Figure 2 It is a tensile test diagram of the graphene thermal control film in Examples 1-3 of the present invention and Comparative Examples 1-3. DETAILED DESCRIPTION

[0032] The specific contents of the present invention are further explained in detail below in conjunction with embodiments.

[0033] Example of preparation of solderable layer

[0034] Preparation Example 1

[0035] A weldable layer consists of 1 part of graphene-modified nano-titanium, 1 part of graphene-modified nano-nickel and 1 part of graphene-modified nano-cadmium.

[0036] Among them, the preparation method of graphene-modified nano-titanium is as follows: 10% of graphene oxide by mass is put into an ethanol solution, ultrasonically vibrated for 5 hours to form a suspension, and then 90% of nano-titanium oxide by mass is put into the suspension and ultrasonically vibrated for 5 hours, and then placed in a drying oven and dried at 80°C for 2 hours to obtain graphene-modified nano-titanium.

[0037] The preparation method of graphene-modified nano-nickel is as follows: 10% graphene oxide by mass is put into an ethanol solution, ultrasonically vibrated for 5 hours to form a suspension, and then 90% nano-nickel by mass is put into the suspension and ultrasonically vibrated for 5 hours, and then placed in a drying oven and dried at 80°C for 2 hours to obtain graphene-modified nano-nickel.

[0038] The preparation method of graphene-modified nano-cadmium is as follows: 10% of graphene oxide by mass is put into an ethanol solution, ultrasonically vibrated for 5 hours to form a suspension, and then 90% of nano-cadmium by mass is put into the suspension and ultrasonically vibrated for 5 hours, and then placed in a drying oven and dried at 80° C. for 2 hours to obtain graphene-modified nano-cadmium.

[0039] Preparation Example 2

[0040] A weldable layer is composed of 5 parts of graphene-modified nano-titanium, 5 parts of graphene-modified nano-nickel, and 5 parts of graphene-modified nano-cadmium.

[0041] Among them, the preparation method of graphene-modified nano-titanium is as follows: 13% of graphene oxide by mass is put into an ethanol solution, ultrasonically vibrated for 5 hours to form a suspension, and then 87% of nano-titanium oxide by mass is put into the suspension and ultrasonically vibrated for 5 hours, and then placed in a drying oven and dried at 80°C for 2 hours to obtain graphene-modified nano-titanium.

[0042] Among them, the preparation method of graphene-modified nano-nickel is as follows: put graphene oxide with a mass fraction of 13% into an ethanol solution, ultrasonically vibrate for 5 hours to form a suspension, then put nano-nickel with a mass fraction of 87% into the suspension and ultrasonically vibrate for 5 hours, put it in a drying oven, and dry it at 80°C for 2 hours to obtain graphene-modified nano-nickel.

[0043] The preparation method of graphene-modified nano-cadmium is as follows: 13% of graphene oxide by mass is put into an ethanol solution, ultrasonically vibrated for 5 hours to form a suspension, and then 87% of nano-cadmium by mass is put into the suspension and ultrasonically vibrated for 5 hours, and then placed in a drying oven and dried at 80° C. for 2 hours to obtain graphene-modified nano-cadmium.

[0044] Preparation Example 3

[0045] A weldable layer is composed of 5 parts of graphene-modified nano-titanium, 5 parts of graphene-modified nano-nickel and 5 parts of graphene-modified nano-cadmium.

[0046] Among them, the preparation method of graphene-modified nano-titanium is as follows: 15% of graphene oxide by mass is put into an ethanol solution, ultrasonically vibrated for 5 hours to form a suspension, and then 85% of nano-titanium oxide by mass is put into the suspension and ultrasonically vibrated for 5 hours, and then placed in a drying oven and dried at 80°C for 2 hours to obtain graphene-modified nano-titanium.

[0047] The preparation method of graphene-modified nano-nickel is as follows: 15% of graphene oxide by mass is put into an ethanol solution, ultrasonically vibrated for 5 hours to form a suspension, and then 85% of nano-nickel by mass is put into the suspension and ultrasonically vibrated for 5 hours, and then placed in a drying oven and dried at 80°C for 2 hours to obtain graphene-modified nano-nickel.

[0048] The preparation method of graphene-modified nano-cadmium is as follows: 15% of graphene oxide by mass is put into an ethanol solution, ultrasonically vibrated for 5 hours to form a suspension, and then 85% of nano-cadmium by mass is put into the suspension and ultrasonically vibrated for 5 hours, and then placed in a drying oven and dried at 80° C. for 2 hours to obtain graphene-modified nano-cadmium.

[0049] Preparation example of graphene layer

[0050] Preparation Example 4

[0051] A method for preparing a graphene layer comprises the following steps:

[0052] 70 parts by weight of modified graphene were put into anhydrous ethanol, and after shaking for 5 hours, a modified graphene suspension was prepared. Then 0.5 parts of nano-diamond particles and 0.1 parts of nano-SiC particles were put into the suspension in turn, and after shaking for 5 hours, they were electrostatically sprayed on a metal substrate, peeled off in water, and finally reduced at a high temperature and high pressure of 2000°C to form a graphene layer. The graphene layer has a thickness of 10μm, a density of 1.1g / cm3, and a thermal conductivity of 2500W / (m·K).

[0053] The modified graphene is prepared by the following method: graphene powder A and graphene powder B in a weight ratio of 1:1 are mixed to obtain mixed graphene oxide, the mixed graphene oxide is added to anhydrous ethanol to prepare a suspension, nematic liquid crystal is added to the suspension, stirred at 40°C for 1 hour, and then dried in a drying oven at 65°C for 40 minutes to obtain the modified graphene; and the weight ratio of the mixed graphene oxide to the nematic liquid crystal is 1:1.5.

[0054] Preparation Example 5

[0055] A method for preparing a graphene layer comprises the following steps:

[0056] 90 parts by weight of modified graphene were placed in anhydrous ethanol, shaken for 5 hours to make a modified graphene suspension, and then 0.8 parts of nano-diamond particles and 0.8 parts of nano-SiC particles were placed in the suspension in turn, shaken for 5 hours, and then electrostatically sprayed on a metal substrate, peeled in water, and finally reduced at 2000°C to form a graphene layer. The thickness of the graphene layer is 2cm and the density is 2g / cm 3 , thermal conductivity is 200W / (m·K).

[0057] The modified graphene is prepared by the following method: graphene powder A and graphene powder B in a weight ratio of 1:1 are mixed to obtain mixed graphene oxide, the mixed graphene oxide is added to anhydrous ethanol to prepare a suspension, nematic liquid crystal is added to the suspension, stirred at 45°C for 1.5 hours, and then dried in a drying oven at 70°C for 1 hour to obtain the modified graphene; and the weight ratio of the mixed graphene oxide to the nematic liquid crystal is 1:1.8.

[0058] Preparation Example 6

[0059] A method for preparing a graphene layer comprises the following steps:

[0060] 99 parts by weight of modified graphene were placed in anhydrous ethanol, and after shaking for 5 hours, a modified graphene suspension was prepared. Then, 1 part of nano-diamond particles and 1 part of nano-SiC particles were placed in the suspension in turn, and after shaking for 5 hours, they were electrostatically sprayed on a metal substrate, peeled off in water, and finally reduced at a high temperature and high pressure of 2000°C to form a graphene layer. The thickness of the graphene layer is 5 cm and the density is 2.5 g / cm 3 , thermal conductivity is 2500W / (m·K)

[0061] The modified graphene is prepared by the following method: graphene powder A and graphene powder B in a weight ratio of 1:1 are mixed to obtain mixed graphene oxide, the mixed graphene oxide is added to anhydrous ethanol to prepare a suspension, nematic liquid crystal is added to the suspension, stirred at 50°C for 2h, and then dried in a drying oven at 75°C for 1h to obtain the modified graphene; and the weight ratio of the mixed graphene oxide to the nematic liquid crystal is 1:2.

[0062] Comparative preparation example of graphene layer

[0063] Comparative Preparation Example 1

[0064] A method for preparing a graphene layer is carried out according to the method in Preparation Example 4, except that the weight of graphene powder B in the modified graphene raw material is replaced by graphene powder A.

[0065] Comparative Preparation Example 2

[0066] A method for preparing a graphene layer is carried out according to the method in Preparation Example 4, except that the weight of modified graphene in the graphene layer raw material is replaced by a mixed graphene oxide obtained by mixing graphene powder A and graphene powder B in a weight ratio of 1:1.

[0067] Example

[0068] Example 1

[0069] A method for preparing a high thermal conductivity graphene thermal control film with a weldable layer comprises the following steps:

[0070] The weldable layer prepared by the method in Preparation Example 1 is mechanically pressed into a target material for magnetron sputtering, and then the target material is magnetron sputtered onto the upper and lower surfaces of the graphene layer prepared by the method in Preparation Example 4, respectively, to obtain a graphene thermal control film, wherein the sputtering time is 30 minutes, the temperature is 150°C, and the sputtering power is 100W; and the thermal conductivity of the weldable layer is 200W / (m·K), and the thickness is 500nm.

[0071] Example 2

[0072] A method for preparing a high thermal conductivity graphene thermal control film with a weldable layer comprises the following steps:

[0073] The weldable layer prepared by the method in Preparation Example 2 is mechanically pressed into a target material for magnetron sputtering, and then the target material is magnetron sputtered onto the upper and lower surfaces of the graphene layer prepared by the method in Preparation Example 5, respectively, to obtain a graphene thermal control film, wherein the sputtering time is 30 minutes, the temperature is 150°C, and the sputtering power is 100 W; and the thermal conductivity of the weldable layer is 200 W / (m·K) and the thickness is 500 nm.

[0074] Example 3

[0075] A method for preparing a high thermal conductivity graphene thermal control film with a weldable layer comprises the following steps:

[0076] The weldable layer prepared by the method in Preparation Example 3 is mechanically pressed into a target material for magnetron sputtering, and then the target material is magnetron sputtered onto the upper and lower surfaces of the graphene layer prepared by the method in Preparation Example 6, respectively, to obtain a graphene thermal control film, wherein the sputtering time is 30 minutes, the temperature is 150°C, and the sputtering power is 100 W; and the thermal conductivity of the weldable layer is 200 W / (m·K), and the thickness is 500 nm.

[0077] Comparative Example

[0078] Comparative Example 1

[0079] A high thermal conductivity graphene thermal control film with a weldable layer is prepared according to the method in Example 1, except that the weight of the nano-diamond particles in the graphene layer is replaced by nano-diamond particles.

[0080] Comparative Example 2

[0081] A high thermal conductivity graphene thermal control film with a weldable layer is prepared according to the method in Example 1, except that the graphene layer in the raw material is prepared by the method in Comparative Preparation Example 1.

[0082] Comparative Example 3

[0083] A high thermal conductivity graphene thermal control film with a weldable layer is prepared according to the method in Example 1, except that the graphene layer in the raw material is prepared by the method in Comparative Preparation Example 2.

[0084] Performance Testing

[0085] The above-mentioned embodiments and comparative examples were tested for brazing rate, tensile strength, operating temperature range, surface thermal conductivity and longitudinal thermal conductivity. The test results are shown in Table 1.

[0086] Table 1:

[0087]

[0088] Figure 2 The tensile test diagram of the graphene thermal control film in Examples 1-3 and Comparative Examples 1-3 of the present invention is shown in FIG. Figure 2 It can be seen that compared with comparative examples 1-3, the tensile stresses of embodiments 1-3 of the present invention are 85 MPa, 88 MPa, and 92 MPa, which are significantly higher than those of comparative examples 1-3, indicating that the graphene thermal control film in the present invention effectively improves the tensile strength.

Claims

1. A high thermal conductivity graphene thermal control film with a weldable layer, characterized in that: It comprises a three-layer structure arranged in sequence, the middle layer structure is a graphene layer, and the upper and lower layers are both weldable layers; The graphene layer is prepared from modified graphene, nano-diamond particles and nano-SiC particles, wherein the modified graphene is obtained by modifying mixed graphene oxide with nematic liquid crystal and reducing it at high temperature, and the mixed graphene oxide includes graphene powder A with a particle size of 0.01 μm and graphene powder B with a particle size of 0.5-3 μm; The raw materials of the weldable layer include graphene-modified nano-titanium, graphene-modified nano-nickel and graphene-modified nano-cadmium; The graphene layer is prepared by the following method: 70-99 parts by weight of modified graphene is placed in anhydrous ethanol, and after shaking, a modified graphene suspension is prepared; 0.5-1 parts of nano-diamond particles and 0.1-1 parts of nano-SiC particles are placed in the suspension in sequence; after shaking, the suspension is electrostatically sprayed on a metal substrate; the suspension is peeled off in water; and finally, the graphene layer is formed by high temperature and high pressure reduction at 1800-2500°C; The modified graphene is prepared by the following method: mixing graphene powder A and graphene powder B in a weight ratio of 1:1 to obtain mixed graphene oxide, adding the mixed graphene oxide into anhydrous ethanol to prepare a suspension, adding nematic liquid crystal into the suspension, stirring at 40-50° C. for 1-2 hours, and drying at 65-75° C. to obtain the modified graphene; and the weight ratio of the mixed graphene oxide to the nematic liquid crystal is 1:(1.5-2); The nematic liquid crystal is one of nematic liquid crystal A, nematic liquid crystal B, and nematic liquid crystal C; The molecular formula of nematic liquid crystal A is as follows: ; The molecular formula of nematic liquid crystal B is as follows: ; The molecular formula of nematic liquid crystal C is as follows: 。 2. A high thermal conductivity graphene thermal control film with a weldable layer as claimed in claim 1, characterized in that: The thickness of the graphene layer is between 10 μm and 5 cm, and the density is between 1.1 and 2.5 g / cm 3 , thermal conductivity is between 800~2500W / (m·K).

3. The high thermal conductivity graphene thermal control film with a weldable layer as claimed in claim 1, characterized in that: The nano-diamond particles have a particle size of 40-100 nm, a thermal conductivity of 2000-2500 W / (m·K), and an expansion coefficient of 1.3-2.3×10 -6 K -1 ; The nano-SiC particles have a particle size of 40-100 nm, a thermal conductivity of 200-400 W / (m·K), and an expansion coefficient of 1×10 -6 K -1 ~5×10 -6 K -1 .

4. The high thermal conductivity graphene thermal control film with a weldable layer as claimed in claim 1, characterized in that: The weight ratio of graphene-modified nano-titanium, graphene-modified nano-nickel and graphene-modified nano-cadmium in the weldable layer is 1:1:

1.

5. The high thermal conductivity graphene thermal control film with a weldable layer as claimed in claim 1, characterized in that: The graphene-modified nano-titanium is prepared by the following method: firstly, 10-15% of graphene oxide by mass is put into an ethanol solution, ultrasonically vibrated to form a suspension, then 85-90% of nano-titanium by mass is put into the suspension, ultrasonically vibrated, and dried to obtain the graphene-modified nano-titanium.

6. The high thermal conductivity graphene thermal control film with a weldable layer as claimed in claim 1, characterized in that: The graphene-modified nano-nickel is prepared by the following method: firstly, 10-15% of graphene oxide by mass is put into an ethanol solution, and after ultrasonic vibration forms a suspension, 85-90% of nano-nickel by mass is put into the suspension and ultrasonic vibration is performed, and the graphene-modified nano-nickel is obtained after drying.

7. The high thermal conductivity graphene thermal control film with a weldable layer as claimed in claim 1, characterized in that: The graphene-modified nano-cadmium is prepared by the following method: firstly, 10-15% of graphene oxide is put into an ethanol solution, ultrasonically vibrate to form a suspension, then 85-90% of nano-cadmium is put into the suspension, ultrasonically vibrate, and dry to obtain the graphene-modified nano-cadmium.

8. A method for preparing a high thermal conductivity graphene thermal control film with a weldable layer as claimed in claim 1, characterized in that: The method comprises the following steps: mechanically pressing the weldable layer into a target material for magnetron sputtering, and then respectively magnetron sputtering the target material onto the upper surface and the lower surface of the graphene layer to obtain a graphene thermal control film.